Self Regulation in Construction Industry; Tacing the Conceptual Islamic Farmework - Zuhairah Ariff, Abd Ghadas; Wan Izzat, Wan Ahmad; Ainul Jariah, Maidin (2014)
The emergence of self-regulation as a mode of regulatory mechanism has in fact spread to being an important dimension in regulating various industries. Despite some reservations on the part of the industries’ stakeholders on the advantages of self-regulation, self-regulatory mechanisms are capable to attract private actors to self-regulate. Industry self-regulation is not a foreign practice in Islam and it is spread out in various operational fields. This paper aims to assess the role of the hisbah institution in ensuring ethical practices on the part of the professionals. The aim is to correct the erroneous impression that the institution is meant only to serve spiritual and social purposes in the society devoid of economic contribution. A literature review approach is adopted to describe the economic dimension of the institution and its specific role in ensuring that businesses are conducted in line with Islamic ethics. The concepts of self-regulation promoted by Islamic law that has been adopted to regulate the economic sector and market principles is analysed to propose a framework for industry self-regulation based on the principles of Islamic law. This paper attempts to fill the vacuum in the contemporary literature on the role of hisbah in promoting accountability in the Muslim societies.